2022
DOI: 10.1371/journal.pone.0270800
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a motivated, action-based intervention on improving physical activity level, exercise self-efficacy and cardiovascular risk factors of patients with coronary heart disease in Sri Lanka: A randomized controlled trial protocol

Abstract: Background Coronary heart disease (CHD), is the major contributor to cardiac-associated mortality worldwide. Lifestyle modification, including physical activity, is highly recommended for secondary prevention for patients with CHD. However, many people in Sri Lanka with CHD do not engage in adequate physical activity. Objective To develop a culture-specific, motivated, and action-based intervention and examine its effects on physical activity level, exercise self-efficacy, and cardiovascular risk factors amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Finally, the results of the present study emphasized the improvement of the physical activity status in the T2D patients participating in a theory-based online educational intervention, which was in line with the results of previous studies [33,36,37]. A systematic review of 52 studies focusing on web-based behavior change interventions by Lin et al (2022) indicated that providing strategies such as self-monitoring of behavior, problem solving, while significantly increasing the mean of the HAPA model constructs and Self-regulation, led to an improvement in the level of physical activity in patients with chronic diseases [36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, the results of the present study emphasized the improvement of the physical activity status in the T2D patients participating in a theory-based online educational intervention, which was in line with the results of previous studies [33,36,37]. A systematic review of 52 studies focusing on web-based behavior change interventions by Lin et al (2022) indicated that providing strategies such as self-monitoring of behavior, problem solving, while significantly increasing the mean of the HAPA model constructs and Self-regulation, led to an improvement in the level of physical activity in patients with chronic diseases [36].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the findings of previous researches, the results of the present study also showed a significant increase in the mean of the action and maintenance self-efficacy constructs in the T2D patients after participating in the mobile-based educational program based on the HAPA model [36][37][38]. People who have strong beliefs about their abilities show more effort and persistence in doing tasks than people who doubt their abilities, and as a result, their performance in doing tasks is better.…”
Section: Discussionsupporting
confidence: 91%
“…Although a sedentary lifestyle places an individual at greater risk for development of various disorders and diseases, regular exercise is often associated with a wider variety of psychological and physical health benefits [9,19,20]. According to the American Association of cardiovascular and pulmonary rehabilitation (AACVPR) in 1999, physical inactivity has been declared the most prevalent NCD risk factor [37].…”
Section: Noncommunicable Disease (Ncd) Risk Factorsmentioning
confidence: 99%
“…These findings are linked to the purpose of using Action-Based Research to promote changes by teachers. Using action-based research as a methodology is conducted by researchers to encourage buy-in groups and mitigate stress and anxiety [34,35].…”
Section: Discussionmentioning
confidence: 99%